Major declines in NE Atlantic plankton contrast with more stable populations in the rapidly warming North Sea - Matthew M. Holland; Arnaud Louchart; Luis Felipe Artigas; Clare Ostle; Angus Atkinson; Isabelle Rombouts; Carolyn A. Graves; Michelle Devlin; Birgit Heyden; Margarita Machairopoulou; Eileen Bresnan; Jos Schilder; et al. (Science of The Total Environment, 2023)

Modeling of Water Quality Indicators in the Western Baltic Sea: Seasonal Oxygen Deficiency - Sarah Piehl; René Friedland; Birgit Heyden; Wera Leujak; Thomas Neumann; Gerald Schernewski (Environmental Modeling & Assessment, 2023)
Hypoxia in coastal seas is a severe threat to marine ecosystems, with the Baltic Sea exhibiting the largest hypoxic areas worldwide. While perennial oxygen deficiency in the deep basins is a component of environmental assessments, seasonal oxygen deficiency in shallow areas is not routinely assessed. Current measurements alone cannot provide the spatio-temporal resolution needed for highly dynamic seasonal oxygen deficiency, making estimations on its duration and extent uncertain. Utilizing long-term 3D model simulations with a horizontal resolution of 3 nautical miles, we analyzed the development of seasonal oxygen deficiency in the western Baltic Sea. Different metrics (near-bottom area, water volume, duration, and frequency) and critical oxygen concentrations were analyzed for exemplary sub-basins as defined by the Helsinki Commission. Our results indicate that the extent of seasonal oxygen deficiency has continually increased in the second half of the twentieth century until the end of the 1980s and slightly decreased in the last two decades. In the 1950s, the spatial extent of oxygen deficiency was still at a low plateau before increasing, indicating that this period could be suitable as a reference period representing a good status, including naturally occurring oxygen deficiency. Overall, seasonal oxygen deficiency is a suitable indicator for describing the ecological status of the western Baltic Sea. For an application as eutrophication indicator in shallow areas, a sufficient spatio-temporal resolution of seasonal oxygen deficiency is needed which can be gained by a combination of model simulations and measurements. Further analysis is needed to integrate in situ measurements and model results to obtain the most reliable approach.

Status of pelagic habitats within the EU-Marine Strategy Framework Directive: Proposals for improving consistency and representativeness of the assessment - Chiara Magliozzi; Marco Palma; Jean-Noël Druon; Andreas Palialexis; McQuatters-Gollop Abigail; Varkitzi Ioanna; González- Quirós Rafael; Gorokhova Elena; Heyden Birgit; Boicenco Laura; Artigas Luis Felipe (Marine Policy, 2023)